Developing the culture of ethics in population health intervention research in Canada. (December 2020) - Hamelin, Anne-Marie; Caux, Chantal; Désy, Michel; Guichard, Anne; Ouédraogo, Samiratou; Tremblay, Marie-Claude; Vissandjée, Bilkis; Godard, Béatrice
Population health intervention research (PHIR) is a particular field of health research that aims to generate knowledge that contributes to the sustainable improvement of population health by enabling the implementation of cross-sectoral solutions adapted to social realities. Despite the ethical issues that necessarily raise its social agenda, the ethics of PHIR is still not very formalized. Unresolved ethical challenges may limit its focus on health equity. This contribution aims to highlight some of these issues and calls on researchers to develop a culture of ethics in PHIR. Three complementary ways are proposed: to build an ethical concept specific to this field, to promote a shared space for critical reflection on PHIR ethics, and to develop the ethical competence in PHIR for which a preliminary framework is proposed.